Implementation of Token Parsing Technique for Regex Based Classification of Unstructured Data for Cyber Threat Analysis - Mohd Pakhari M.H.; Jamil N.; Rusli M.E.; Abdul Rahim A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data handling; Engines; Information use; Pattern matching; Cyber threats; Public resources; Structured data; Threat analysis; Unstructured data; Classification (of information)